Seizure of Property as a Way to Ensure Compensation for Damage Caused by a Crime: Theory and Practice - Dmitriy Aleksandrovich Ivanov; Marina Vladimirovna Sokolova; Oksana Leonidovna Podustova; Pavel Vladimirovich Fadeev; Alexey Yurievich Molyanov (Jurnal Cita Hukum, 2021)
The authors consider the theoretical provisions and analyze practical examples of the activities of the investigative bodies to seize property in pre-trial proceedings in criminal cases. The relevance of this topic is determined by the fact that one of the priority activities of the preliminary investigation bodies at present is to ensure the rights and legitimate interests of citizens against criminal encroachments. The possibility of compensation to victims of harm caused by a crime in criminal procedure law is a guarantee of protection of these rights and contributes to the implementation of the purpose of criminal proceedings. Based on the results obtained, the authors conclude that it is necessary to further improve the law enforcement practice and the norms of criminal and criminal-procedure legislation in order to improve the efficiency of solving problems of identifying property that can be seized. In this connection, it is proposed to amend Part 3 of Article 104.1 of the Criminal Code of the Russian Federation, providing for the possibility of confiscation of property, regardless of the awareness of the causal relationship between the committed act and the presence of money or other property.Keywords: Criminal proceedings; Measures of procedural coercion; Investigator; Inquirer; Civil claim Penyitaan Properti sebagai Cara untuk Memastikan Kompensasi atas Kerusakan yang Disebabkan oleh Kejahatan: Teori dan Praktik AbstrakPenulis mempertimbangkan ketentuan teoritis dan menganalisis contoh praktis dari kegiatan badan investigasi untuk menyita properti dalam proses pra-persidangan dalam kasus pidana. Relevansi topik ini ditentukan oleh fakta bahwa salah satu kegiatan prioritas badan investigasi pendahuluan saat ini adalah memastikan hak dan kepentingan sah warga negara terhadap perambahan kriminal. Kemungkinan pemberian ganti rugi kepada korban kerugian yang diakibatkan oleh suatu tindak pidana dalam hukum acara pidana merupakan jaminan perlindungan terhadap hak-hak tersebut dan turut menunjang terlaksananya tujuan proses pidana. Berdasarkan hasil yang diperoleh, penulis menyimpulkan bahwa perlu lebih meningkatkan praktik penegakan hukum dan norma-norma peraturan perundang-undangan pidana dan acara pidana untuk meningkatkan efisiensi penyelesaian masalah identifikasi harta benda yang dapat disita. Sehubungan dengan itu, diusulkan untuk mengubah Bagian 3 Pasal 104.1 KUHP Federasi Rusia, yang mengatur kemungkinan penyitaan properti, terlepas dari kesadaran akan hubungan sebab akibat antara tindakan yang dilakukan dan adanya uang atau properti lainnya.Kata Kunci: Proses pidana; Tindakan paksaan prosedural; Peneliti; Penanya; Klaim sipil. Наложение ареста на имущество в целях обеспечения возмещения вреда, причиненного преступлением: теория и практика АннотацияАвторами рассматриваются теоретические положения и анализируются практические примеры деятельности органов расследования по наложению ареста на имущество в досудебном производстве по уголовным делам. Актуальность данной темы определяется тем, что одним из приоритетных направлений деятельности органов предварительного следствия в настоящее время является обеспечение прав и законных интересов граждан от преступных посягательств. Возможность возмещения потерпевшим вреда, причиненного преступлением, в уголовно-процессуальном праве является гарантией защиты данных прав и способствует реализации назначения уголовного судопроизводства. На основе полученных результатов авторы приходят к выводу о необходимости дальнейшего совершенствования правоприменительной практики и норм уголовного и уголовно-процессуального законодательства в целях повышения эффективности решения задач по установлению  имущества, на которое может быть наложен арест. В связи с чем предлагают внести в ч. 3 ст. 104.1 УК РФ изменения, предусматривающие возможность конфискации имущества, вне зависимости от осведомленности о причинно-следственной связи между совершенным деянием и наличием денег или иного имущества.Ключевые слова: Ключевые слова: уголовное судопроизводство, меры процессуального принуждения, следователь, дознаватель, гражданский иск